Aplikasi Pemberian Pupuk Kompos dan Biochat untuk Bunga Bungenvil di Pot pada Kelompok Ibu-Ibu PKK RT 23 Kelurahan Pasir Putih Kota Jambi - Suryanto; Yusfaneti; Hasriati Nasution; Asmadi Saat (WIDA Publishing, 2025)
Bougainvillea, commonly known as paper flower, is widely used to enhance environmental aesthetics due to its bright and attractive flowers. In addition to its ornamental value, this plant also provides benefits for health and the environment. Proper cultivation of bougainvillea is essential to achieve healthy growth and abundant flowering. One of the key factors for successful plant growth is the use of appropriate growing media with a loose structure, good drainage, and sufficient essential nutrients. Compost fertilizer is an organic fertilizer produced through the controlled decomposition of organic materials by microorganisms, which is beneficial for improving soil structure and nutrient availability. In addition to compost, the application of biochar to the growing media significantly contributes as a soil amendment by improving both chemical and physical soil properties, while also enhancing the soil’s water-holding capacity. Through this community service activity, members of the PKK women’s group of RT 23, Pasir Putih Subdistrict, Jambi City, were provided with educational materials and hands-on demonstrations on the proper use of compost and biochar in bougainvillea cultivation. The activities resulted in increased knowledge and practical skills among the participants and are expected to provide long-term social and environmental benefits. Strengthening skills in ornamental plant cultivation through the use of appropriate and high-quality organic inputs is also important in supporting household-based productive activities within the community.Bottom of Form